Mass spectrometry of organic matter influenced by long-term pedogenesis and a short-term reclamation practice in an Oxisol of Brazil - Monreal, Carlos M.; Alves, Marlene Cristina [UNESP]; Schnitzer, Morris; Souto Filho, Sebastiao Nilce [UNESP]; Batista Bonini, Carolina dos Santos [UNESP] (Agricultural Inst Canada, 2016)
Little is known about the influence of soil pedogenesis and reclamation practices on the chemical composition of soil organic matter (SOM) in eroded Oxisol. We examined the long-term influence of pedogenesis and 8 years of a reclamation practice on SOM in the top 5 cm of an artificially eroded Oxisol of Brazil. The experimental site involved replicated treatments established under native vegetation, and an adjacent site whose top 8.6 m had been removed mechanically (eroded reference). The eroded Oxisol was under reclamation with native tree and grass species, and addition of sewage sludge. Pyrolysis field ionization mass spectrometry was used to characterize SOM. The abundance of most classes of SOM and soil carbon decreased in the following order: native > reclaimed >> eroded soil. Relative to the eroded reference, SOM in the native soil was highly humified and stabilized by inorganic colloids of iron, aluminum, and silicon. Humified and thermally stable SOM in the native and reference eroded soils involved mostly alkylaromatics, lipids, phenols+lignin monomers, lignin dimers, and N-heterocyclics. The reclaimed soil SOM was less humified and less stable than the native Oxisol, showing significant contributions of carbohydrates, amino acids, and sterols derived from sewage sludge and plant residues.
Keywords: oxisol; soil organic matter; chemical classes; mass spectrometry; erosion; soil reclamation